ROLE OF ECONOMIC RESOURCES AND FAMILY ENVIRONMENT: A CRITICAL STUDY OF THE EDUCATIONAL PROGRESS OF SCHEDULED TRIBE HIGH SCHOOL STUDENTS IN CHHINDWARA DISTRICT - Jawre, Priti; Chaturvedi, Prakriti (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study presents a critical analysis of the impact of economic resources and family environment on the educational progress of scheduled tribe high school students in Chhindwara district. Based on a sample of 350 students, this study evaluated the relationship between economic status, family environment and their educational achievement. The results revealed that lack of economic resources and imbalanced family environment are hindrances to the educational progress of students. Finally, the study also provides policy suggestions to strengthen the education of ST students.